Diversity management and the business case - Michael Fischer (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
Managing for diversity is a management strategy that intends to make productive use of (ethnic and other) differences between individuals. It is based on the premise that - at least if they are well managed - diverse teams will produce better results and diverse companies will gain market advantage. In contrast to other employment equity policies, diversity management is primarily driven by the business case, i.e. by the argument that diversity and/or its management will increase organizational efficiency and profitability. With diversity management as a business practice becoming more and more popular in Europe, the question of whether this policy actually delivers the business benefits its advocates promise, becomes increasingly relevant to anyone involved in the discussion and implementation of employment policies relating to ethnic and other minorities. An examination of the literature, however, shows that there is no unanimous answer regarding the business benefits of diversity and its management. While for many advocates of diversity management the business case seems to be rather self-evident, academic research on the effects of diversity provides mixed and inconclusive results and has led critics to see a mismatch between research results and diversity rhetoric (Kochan et al 2003: 5).
Keywords: 330